Analysis of First-Time Voter Characteristics in the 2024 Legislative Election in Jayawijaya Regency: A Perspective of Local Wisdom and Political Culture - Siti Khikmatul Rizqi; Renida Jozelina Torobi; Rekno Sulandjari; Putera Astomo (JURNAL AKTA, 2026)
Research on the characteristics of first voters in the Legislative Election in Jayawijaya Regency is essential for understanding the political preferences of young voters, formulating effective campaign strategies, evaluating the success of political socialization, increasing voter participation, and supporting more accurate public policy planning. This study aims to analyze the characteristics of first voters in the 2024 Legislative Election in Jayawijaya Regency. The research employs a descriptive method with a qualitative approach. A total of 30 informants were selected using purposive sampling techniques. Data were collected through observation, in-depth interviews, and documentation, then analyzed using qualitative analysis stages, including data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that first voters in Jayawijaya tend to exhibit two types of characteristics: primordial and rational. However, the dominant tendency remains within the primordial type, where voting decisions are primarily influenced by similarities in religion, ethnicity, or tribe.